Secrecy in concurrent version control systems - Pellegrini, Jerônimo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2006: Anais do VI Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2006.20953, 2006)
This paper describes two cryptographic protocols for incorporating secrecy in concurrent version control systems in such a way that neither text nor passphrases are ever sent to possibly hostile servers. One of the protocols works for centralized and one for distributed version control systems. Most operations, as defined by the protocols, take linear time on the size of keys or the size of changes made to the content, and the most frequent ones do not depend on the number of users. Both protocols rely on a public key infrastructure for access control.